Sobre Agustín Sánchez Andrés, Rosario Rodríguez Díaz, Fernando Alanis Enciso y Enrique Camacho Navarro (coords.), Artífices y operadores de la diplomacia mexicana, siglos XIX y XX - Enciso Higuera, Froylán V. (Historia Mexicana, 2009)
-